Pirfenidone in idiopathic pulmonary fibrosis - Taniguchi, H; Ebina, M; Kondoh, Y; Ogura, T; Azuma, A; Suga, M; Taguchi, Y; Takahashi, H; Nakata, K; Sato, A; Takeuchi, M; Raghu, G; et al. (The European respiratory journal, 2010)
Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease without proven effective therapy. A multicentre, double-blind, placebo-controlled, randomised phase III clinical trial was conducted in Japanese patients with well-defined IPF to determine the efficacy and safety of pirfenidone, a novel antifibrotic oral agent, over 52 weeks. Of 275 patients randomised (high-dose, 1,800 mg·day −1 ; low-dose, 1,200 mg·day −1 ; or placebo groups in the ratio 2:1:2), 267 patients were evaluated for the efficacy of pirfenidone. Prior to unblinding, the primary end-point was revised; the change in vital capacity (VC) was assessed at week 52. Secondary end-points included the progression-free survival (PFS) time. Significant differences were observed in VC decline (primary end-point) between the placebo group (-0.16 L) and the high-dose group (-0.09 L) (p = 0.0416); differences between the two groups (p = 0.0280) were also observed in the PFS (the secondary end-point). Although photosensitivity, a well-established side-effect of pirfenidone, was the major adverse event in this study, it was mild in severity in most of the patients. Pirfenidone was relatively well tolerated in patients with IPF. Treatment with pirfenidone may decrease the rate of decline in VC and may increase the PFS time over 52 weeks. Additional studies are needed to confirm these findings.